Superior Mesenteric Vein Occlusion Causing Severe Gastrointestinal Haemorrhage in Two Paediatric Cases. (6th November 2012) - Fox, Anna L.; Jones, Matthew; Healey, Andrew; Auth, Marcus K. H.
Abstract : Reports about superior mesenteric vein thrombosis in childhood are very rare and have not been associated with gastrointestinal bleeding. We describe two cases of severe bleeding from the upper and lower gastrointestinal tract in children who had undergone complex abdominal surgery at considerable time before. The first child had a tracheoesophageal fistula, corrected by division, gastrostomy insertion, and repair of duodenal rupture. The child presented with severe bleeding from the gastrostomy site and was diagnosed with a thrombosis of the proximal superior mesenteric vein. The second child had a gastroschisis and duodenal atresia, and required duodenoplasty, gastrostomy insertion, hemicolectomy, and adhesiolysis. The child presented with intermittent severe lower gastrointestinal bleeding, resulting from collateral vessels at location of the surgical connections. He was diagnosed with a thrombosis of the superior mesenteric vein. In both children, the extensive previous surgery and anastomosis were considered the cause of the mesenteric thrombosis. CT angiography confirmed the diagnosis in both cases, in addition to characteristic findings on endoscopy. Paediatricians should suspect this condition in children with severe gastrointestinal bleeding, particularly in children with previous, complex abdominal surgery.